Critical Literacy and its Challenges in Education in Indonesia - Patria, Rida (EDUPEDIA Publisher, 2022)
Reading is one of the four language skills that should be mastered by students. Dadzie (2008) states that reading is the ability to understand words contained in a document and make use of the knowledge for personal growth and development. Bahadır (2012) claims that in today’s societies, reading has considered as indispensable for a life of high quality. By reading, students will gain new understanding, new ideas, and also new knowledge that can expand their views later. Literacy culture will lead to critical literacy. The term of Critical Literacy arises from the results of research that has been conducted by Freire, an education expert from Brazil, who concluded that literacy learning should focus on reading words and reading the world or reading texts and contexts. This research was carried out using a review of the literature. A literature review is a description of the theory, findings, and other research materials obtained from reference materials that will be used to guide research activities. A literature review includes reviews, summaries, and the author's thoughts on various sources of literature (articles, books, slides, internet information, and so on) on the topics discussed. A good literature review must be current and relevant.